AIRCRAFT MAINTENANCE ROUTING PROBLEM - A LITERATURE SURVEY - TUZKAYA, GÜLFEM; VAYVAY, ÖZALP (SVENCILISTE U ZAGREBU, FAKULTET PROMETNIH ZNANOSTI, 2021)
The airline industry has shown significant growth in the last decade according to some indicators such as annual average growth in global air traffic passenger demand and growth rate in the global air transport fleet. This inevitable progress makes the airline industry challenging and forces airline companies to produce a range of solutions that increase consumer loyalty to the brand. These solutions to reduce the high costs encountered in airline operations, prevent delays in planned departure times, improve service quality, or reduce environmental impacts can be diversified according to the need. Although one can refer to past surveys, it is not sufficient to cover the rich literature of airline scheduling, especially for the last decade. This study aims to fill this gap by reviewing the airline operations related papers published between 2009 and 2019, and focus on the ones especially in the aircraft maintenance routing area which seems a promising branch.
Keywords: airline operations; airline scheduling; aircraft maintenance routing; INTEGRATED FLEET ASSIGNMENT; SAFETY MANAGEMENT-SYSTEM; TERMINAL CONTROL AREA; HEURISTIC ALGORITHM; SINGLE FLEET; ROBUST; CREW; OPTIMIZATION; MODEL; IMPLEMENTATION